Clinical outcome of the Gant-Miwa-Thiersch procedure for colonic mucosal prolapse after intersphincteric resection—a single-center report from Japan. (December 2021) - Nitta, Toshikatsu; Ishii, Masatsugu; Kataoka, Jun; Senpuku, Sedakatsu; Ueda, Yasuhiko; Iida, Ryo; Matsutani, Ayumi; Ishibashi, Takashi
Abstract: Introduction: Dysfunctions such as mucosal prolapse occur after intersphincteric resection (ISR) to treat lower rectal cancer, even when it is possible to preserve the anus. Method: We analyzed the data of 12 patients with rectal or colonic prolapse who underwent the Gant-Miwa-Thiersch procedure between March 2017 and May 2021. Result: There were no severe postoperative complications or recurrences. Case presentation: A 75-year-old Japanese man initially underwent ISR and had mucosal prolapse nine months after his initial operation. We performed the Gant-Miwa-Thiersch procedure for colonic mucosal prolapse after ISR. Surgical procedure: Our procedure is a perineal plication method of prolapsed colonic mucosa with nylon wiring (The Gant-Miwa procedure), using a 1-nylon wire encircled three times to straighten the anal canal, with a cord inserted above the internal sphincter muscle (Thiersch procedure). Discussion: Mucosal plication is performed via the Gant-Mowa or Delorme procedure to reduce the risk of recurrence. However, mucosal plication can be performed many times. Our Thiersch procedure involves encircling and straightening the anal canal with a 1-nylon wire to fix the new internal anal sphincter. In conclusion, the Gant-Miwa-Thiersch procedure for rectal and colonic mucosal prolapse, especially after ISR, is a viable treatment option. Highlights: Our procedure is The Gant-Miwa procedure, using a 1-nylon wire encircled three times (Thiersch procedure). Mucosal plication is performed via the Gant-Mowa or Delorme procedure to reduce the risk of recurrence. The Gant-Miwa-Thiersch procedure for rectal and colonic mucosal prolapse, especially after ISR, is a viable treatment option.